Here's the question you clicked on:

55 members online
  • 0 replying
  • 0 viewing

cece_lovely

  • 4 years ago

can some one simplify this 4 me? so i understand a lil more. (x^2+2x over 12x+54) -(3-x over 8x+36)

  • This Question is Closed
  1. computergeek123
    • 4 years ago
    Best Response
    You've already chosen the best response.
    Medals 1

    (x² + 2x)/(6(2x + 9)) - (3 - x)/(4(2x + 9)) => (x² + 2x)/(6(2x + 9)) * 2/2 - (3 - x)/(4(2x + 9)) * 3/3 => (2(x² + 2x) - 3(3 - x))/(12(2x + 9)) => (2x² + 4x - 9 + 3x)/(12(2x + 9)) => (2x² + 7x - 9)/(12(2x + 9)) => (2x + 9)(x - 1)/(12(2x + 9)) => (x - 1)/12

  2. cece_lovely
    • 4 years ago
    Best Response
    You've already chosen the best response.
    Medals 1

    thanx sooo much i hate math some times -__- lol

  3. Not the answer you are looking for?
    Search for more explanations.

    • Attachments:

Ask your own question

Sign Up
Find more explanations on OpenStudy
Privacy Policy